Penerapan Telemedisin dengan Program Kunjungan dan Konseling Farmasi Secara Virtual dengan Metode COM-B di Puskesmas Gayamsari Kota Semarang - Sri Suwarni; Zakky Cholisoh; Tri Kamalasari; Karol Giovani Battista Leki (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Telemedicine is a method for improving access, quality, and safety of healthcare services. However, theimplementation of telemedicine, particularly telepharmacy services in primary healthcare facilities suchas community health centers (Puskesmas), is still not structured and regular. This study aims to analyzethe implementation and success of the Virtual Pharmacy Visit and Counseling Program using the COMB(Capability,Opportunity,Motivation–Behavior)approach. Thisstudyusedaprospective,descriptivequalitativemethodwithatriangulationapproach.Thestudy was conducted at the Gayamsari Community Health Center in Semarang City from September toDecember 2025. The informants in this study consisted of three pharmacists directly involved in theimplementation of the innovative telemedicine program. Data were collected through in-depth interviewsand focus group discussions (FGDs), using an interview guide verified through expert assessment. Dataanalysis was conducted thematically based on the COM-B framework.The study results indicate that pharmacists have sufficient skills to conduct online drug counseling andeducation. The opportunity for implementing telepharmacy is supported by national regulations, althoughthere are no specific technical operational guidelines. Motivation from pharmacists and support fromCommunity Health Center (Puskesmas) leaders are the main factors driving the program'simplementation. The implementation of KUFI LUWAK has proven to increase access to pharmacycounseling services, as evidenced by the increase in the number of patients from an average of 10 patientsper month to 47 patients per month. Collaboration between programs and the empathetic use of digitaleducational media also increased patient adherence to therapy. In conclusion, the implementation ofTelemedicine with a Virtual Pharmacy Visit and Counseling Program, analyzed using the COM-B methodat the Gayamsari Community Health Center in Semarang City, successfully implemented a form oftelemedicine service called the KUFI LUWAK Program. This program is considered qualitatively effectiveand has the potential to be implemented elsewhere if supported by more structured policies andoperational standards.